1996
DOI: 10.1095/biolreprod54.5.939
|View full text |Cite
|
Sign up to set email alerts
|

Mucin (Muc-1) Expression is Differentially Regulated in Uterine Luminal and Glandular Epithelia of the Baboon (Papio Anubis)1

Abstract: Changes in the organization and composition of apical cell surface glycoconjugates accompany the transition of luminal epithelial cells from the prereceptive state of the uterus in many species. In spite of the biological and clinical significance of this process, few molecular markers have arisen as useful predictors of uterine receptivity. Recent studies in mice demonstrate that the transmembrane mucin glycoprotein, Muc-1, is abundantly expressed at the apical surface of luminal epithelia under most conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 29 publications
7
62
0
Order By: Relevance
“…The same observations were made in sheep, pigs and baboons, showing that MUC-1 expression is downregulated during the implantation window (12)(13)(14).…”
supporting
confidence: 74%
“…The same observations were made in sheep, pigs and baboons, showing that MUC-1 expression is downregulated during the implantation window (12)(13)(14).…”
supporting
confidence: 74%
“…Sections probed with and without antigen retrieval indicated that tissue processed by formalin fixation and paraffin embedding required a retrieval step in order to optimize detection of Muc-1 with the CT-1 antibody. Application of this staining protocol to formalin-fixed, paraffin-embedded sections from cycling baboon uteri produced the same expression pattern for Muc-1 obtained previously when frozen sections were probed with CT-1 antibody and immunoperoxidase detection (Hild-Petito et al, 1996). Controls, which included nonimmune rabbit IgG or buffer in place of primary antibody, displayed a background due to autofluorescence which could not be quenched or blocked.…”
Section: Antibodiesmentioning
confidence: 61%
“…Researchers have turned to nonhuman primate models in hopes of explaining the perplexing observation that humans appear to be a rare species in which MUC1, the major transmembrane mucin in uteri of most species, does not seem to be reduced in luminal epithelia of the receptive uterus (Aplin et al, 1998;DeLoia et al, 1998). When the temporal and spacial expression of cell-associated Muc-1 core protein was examined in baboon (Papio anubis) uteri during non-conceptual cycles (Hild-Petito et al, 1996), Muc-1 was upregulated in luminal epithelium of baboon uterus during the early luteal phase in response to progesterone as has been observed in the human uterus (Hey et al, 1994); however, unlike the human, continued exposure to progesterone resulted in loss of both Muc-1 and progesterone receptor from luminal epithelia as the transition to receptivity occurred. In the new world monkey, Cebus apella, Muc-1 was detected on luminal epithelium at day 7 post ovulation (PO) of a non-conceptual cycle .…”
Section: Introductionmentioning
confidence: 99%
“…In mice, Muc1 expression is stimulated by E2 and repressed by P4 (Surveyor et al 1995). Regulation of Muc1 expression in pigs is similar to mice (Bowen et al 1996) while in baboons and rabbits it is by P4 only (Bowen et al 1996), in baboons and rabbits, by P4 only (Hild-Petito et al 1996, Hoffman et al 1998. However, the expression pattern of Muc1 in the endometrium shows species to species variation.…”
Section: Mucin 1 (Muc1)mentioning
confidence: 98%